This is a moose - Morris, Richard T., 1969- (Little, Brown and Company, 2014)
Director Billy Waddler is trying to film a documentary about moose, but the moose in question has no intention of spending his life in the woods and his animal friends, who have dreams of their own, help him prove his point.